Tourist plans for urban residents at the time of the COVID-19 pandemic - Zawadka, Jan; Jęczmyk, Anna; Uglis, Jarosław; Wojcieszak-Zbierska, Monika Małgorzata (Turystyka i krajoznawstwo, 2021)
The aim of the study is to present the tourist plans of the inhabitants of Polish cities during the COVID-19 pandemic. A survey technique was used in the research with a questionnaire being disseminated for Facebook´s tourist thematic groups. Those recruited provided their friends with a link to the questionnaire via social media. Thus a snowball method was used and 402 respondents were obtained. Less than a quarter declared they did not want to go on a tourist trip in 2020 and the main reason was the prevailing pandemic and fear of coronavirus infection. However, the vast majority of respondents planned at least one tourist trip but a significant part abandoned any intention of travelling abroad for a holiday. The respondents mainly declared their willingness to stay in hotels and holiday resorts but assessed these facilities as the least safe in terms of epidemiology. The prevailing pandemic has been a source of much concern but the respondents were also worried about increased prices. Accommodation facilities were expected to undergo some form of disinfection along with the need to comply with social distancing restrictions and the wearing of masks.